Evaluation of air quality in food courts by determining the presence of airborne bacteria and fungi / Nur Izzati Shamsudin, Ahmad Razali Ishak and Maimunah Mustakim - Shamsudin, Nur Izzati; Ishak, Ahmad Razali; Mustakim, Maimunah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Bacterial and fungal bioaerosols are ubiquitous in the environment. Humans are frequently exposed to bioaerosol-derived airborne pollutants that cause respiratory illness. Therefore, investigation of microorganisms in the air environment is essential for assessing air quality and controlling potential health risks. The study aims to a) identify airborne bacteria and fungi and b) examine the relationship between airborne bacteria and fungi concentrations with environmental factors from the selected UiTM Puncak Alam food courts. Air samples were collected using the M Air T™Milipore Air Tester. The temperature, relative humidity, and population density were recorded. The findings showed Staphylococcus spp. (63.1%) and Bacillus spp. (28.8%) were found to be the most prevalent bacteria. The dominant isolated fungi were Aspergillus (53.8%), Fusarium (20.5%), and Penicillium (18.8%). There was a substantial variation in the concentration of airborne microorganisms between indoor and outdoor food courts. However, the microbes discovered were not tested for their pathogenic attributes. The acquired results indicated that food courts at UiTM Puncak Alam are hygienic, as the concentration of microorganisms is below the maximum suggested range. In conclusion, continuous preventive measures, such as ventilation system maintenance and scheduled regular cleaning must be employed to control all variables that accelerate microbial growth.